Managing More-than-Moore Integration Technology Development A Story of an Advanced Technology Program in the Semiconductor Industry - Radojcic, Riko (Springer International Publishing : Imprint: Springer, 2019)
This book presents the real challenges and experiences of managing an advanced semiconductor technology development and integration program - but using a novelized form. The material is presented in a conversational format through a story that follows a fictional narrator as she grows from an intern to a manager in a (fictional) chip company. The story describes the technology development program from management, engineering and human perspectives, and exposes not only the management and technical issues but also the typical work-life balance challenges experienced by engineers working in the technology industry. Use of a series of realistic and representative vignettes, supported by a set of illustrative cartoon-ish panels, presents the serious management topics in a light and readable way. Based on real, hands-on experiences and presents actual lessons learned; Describes various aspects of managing an engineering development program; Explains key technical aspects of semiconductor technology to non-experts; Written in a novelized form that makes it very easy to read; Enables an understanding of how and why the chip industry evolved over the last 50 years into what it is today.